STEEL CORD WITH A COMPLETE PENETRATION OF COMPOUND INTO THE STRUCTURE - A. V. Vedeneev (Литьë и металлургия)
It is shown that one of the perspective types of metal cord for breaker layer of automobile tires are the constructions with maximal degree of rubber compound penetration at vulcanization. the constructions and technologies of metal cord productions with full rubber penetration (FrP) already in the process of treatment into rubber-cord cloth are developed at RUP “BMZ”.